Type 2 Immunity and Age Modify Gene Expression of Coronavirus-induced Disease 2019 Receptors in Eosinophilic Gastrointestinal Disorders. Issue 5 (May 2021) - Chiang, Austin W.T.; Duong, Loan D.; Shoda, Tetsuo; Nhu, Quan M.; Ruffner, Melanie; Hara, Takeo; Aaron, Bailey; Joplin, Erik; Manresa, Mario C.; Abonia, J. Pablo; Dellon, Evan S; Hirano, Ikuo; et al.
Abstract : ABSTRACT: Infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can lead to coronavirus-induced disease 2019 (COVID-19). The gastrointestinal (GI) tract is now an appreciated portal of infection. SARS-CoV-2 enters host cells via angiotensin-converting enzyme-2 (ACE2) and the serine protease TMPRSS2. Eosinophilic gastrointestinal disorders (EGIDs) are inflammatory conditions caused by chronic type 2 (T2) inflammation. the effects of the T2 atopic inflammatory milieu on SARS-COV-2 viral entry gene expression in the GI tract is poorly understood. We analyzed tissue ACE2 and TMPRSS2 gene expression in pediatric eosinophilic esophagitis (EoE), eosinophilic gastritis (EG), and in normal adult esophagi using publicly available RNA-sequencing datasets. Similar to findings evaluating the airway, there was no difference in tissue ACE2/TMPRSS2 expression in EoE or EG when compared with control non-EoE/EG esophagus/stomach. ACE2 gene expression was significantly lower in esophagi from children with or without EoE and from adults with EoE as compared with normal adult esophagi. Type 2 immunity and pediatric age could be protective for infection by SARS-CoV-2 in the gastrointestinal tract because of decreased expression of ACE2. Abstract : Supplemental Digital Content is available in the text